Prospect of big data stimulating business model innovation of telecom operator - Junlin WANG; Baowang WANG; Fei ZHAO; Chunyu MA; Shaofu TAN (Dianxin kexue)
Combined with big data research and practice of telecommunication industry,eight business operation areas in which big data can create values were illustrated.Through explaining the definition and characteristics of big data which stimulates business model innovation,the concept of intelligence operations center was illuminated,and the significance,commercial design and supporting elements were introduced.At the same time,the relationship between intelligence operations center and other business platforms was explained.Finally the development opportunities and evolution strategies of intelligence operations center at AI era was introduced.